Somatic embryogenesis of avocado (Persea americana)and its application for plant improvement - Witjaksono, Litz, R.E.E.
The avocado is cultivated in tropical and subtropical regions of more than 50 countries. Avocado improvement through conventional breeding is slow, especially for resistance to the devastating soil-borne disease Phytophthora root-rot (PRR). Biotechnology can supplement avocado breeding by generating new variability unobtainable using conventional approaches. Therefore, an improved protocol for plant regeneration by somatic embryogenesis has been developed. Culture initiation, maintenance and somatic embryo development have been optimized. Plant regeneration from protoplasts has also been described and somatic hybridization with sexually and asexually incompatible related PRR resistant Persea spp. such as P. cinerascens and P. pachypoda is in progress. Genetic transformation of embryogenic avocado cultures with an anti-fungal protein gene, chitinase and glucanase genes are underway.
Keywords: GENETIC TRANSFORMATION; PROTOPLAST; TISSUE CULTURE